GAMMA RADIATION ANALYSIS ON IN VIVO/ IN VITRO TESTING FACILITY BORON NEUTRON CAPTURE THERAPY - Gabriel Simanjuntak (Indonesian Journal of Physics and Nuclear Applications, 2020)
BNCT is the latest method in nuclear technology that combines chemotherapy and radiotherapy. Therapy that uses ionizing radiation must pay attention to the safety of patients, radiation workers and the environment. Therefore, shielding is needed for radiation protection, especially gamma radiation. A refining for the shielding and the testing had been done to know the limitation for the use of testing facility in vivo / in vitro that meets the NPD/Dose Constraint limitation from PSTA BATAN with parameter shielding radiation outcome, shielding geometry, and energy value Kartini Reactor. The highest measurement result reaches 4.8 mSv/j with 100kW energy. By considering the measurement result with the NPD/Dose Constraint limitation from PSTA BATAN for Kartini Reactor operation, the activity of testing facility in vivo/in vitro can be done 46 times in a year. Keywords : BNCT, Shielding, Gamma Radiation.